The Effect Nitrogen Fertilizer Application on the Resistance of Tobacco (Nicotiana tabacum L. ‘Bligon’) against Drought Stress - Rima Vegi Santika; Siti Nurbaiti; Putra, Sidiq Permana; Rachmawati, Diah (Biotropika: Journal of Tropical Biology, 2025)
Tobacco (Nicotiana tabacum L.) is a plant that has high economic value. Water availability is a challenge in cultivating tobacco plants. Drought can affect plant physiology, reducing the metabolic rate and productivity of tobacco plants. Urea fertilizer contains nitrogen as a macronutrient, which plays a role in vegetative growth and water absorption in drought stress. This research aims to study the resistance response of tobacco to varying conditions of water availability and nitrogen fertilizer application. The water availability treatment provided includes 100%, 75% and 50% of the field capacity. Variations in the dose of nitrogen fertilizer were 0.6 g; 1.2 g; and 1.8 g/polybag. This research was conducted using a Randomized Complete Block Design (RCBD) with three replications. The parameters measured were resistance responses including H?O? content and antioxidant enzyme activity such as SOD, CAT, and APX. The results showed that the more severe the drought, the higher the H?O?  levels. The plant resistance mechanism is indicated by the activity of the antioxidant enzymes SOD, CAT, and APX, despite the fluctuating values observed during the experimental period. The application of nitrogen fertilizer at doses of 0.6 g, 1.2 g, and 1.8 g/polybag showed no significant differences in the physiological responses of the plants. As a result, a dose of 0.6 g/polybag can be recommended as an agronomically and economically efficient.